2021
DOI: 10.3389/fpsyg.2021.709851
|View full text |Cite
|
Sign up to set email alerts
|

Effects and Moderators of Triple P on the Social, Emotional, and Behavioral Problems of Children: Systematic Review and Meta-Analysis

Abstract: Background: Social, emotional, and behavioral problems in childhood are key predictors of persistent problem behaviors throughout the life courses of individuals. Early parental intervention training, as an important preventive measure, plays a critical role in improving the social, emotional, and behavioral (SEB) development of children.Method: We conducted a systematic review and meta-analysis to analyze the intervention effects of the latest literature on Triple P (Positive Parenting Program), which is a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 26 publications
3
23
0
1
Order By: Relevance
“…There is also evidence that the impact of an intervention might tend to be moderated or mediated by the characteristics of the target population (e.g., Lagdon et al, 2021;Rubio-Hernández et al, 2020), the implementation (e.g., Li et al, 2021;Wright et al, 2017), or the evaluation (e.g., Knerr et al, 2013;Ttofi & Farrington, 2011;Vlahovicova et al, 2017). Specifically, the characteristics of implementations are a key factor in understanding a programme's success (Jeong, Franchett, et al, 2021;Mettert et al, 2020).…”
Section: Evidence Of Impacts In Family Support Programmesmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence that the impact of an intervention might tend to be moderated or mediated by the characteristics of the target population (e.g., Lagdon et al, 2021;Rubio-Hernández et al, 2020), the implementation (e.g., Li et al, 2021;Wright et al, 2017), or the evaluation (e.g., Knerr et al, 2013;Ttofi & Farrington, 2011;Vlahovicova et al, 2017). Specifically, the characteristics of implementations are a key factor in understanding a programme's success (Jeong, Franchett, et al, 2021;Mettert et al, 2020).…”
Section: Evidence Of Impacts In Family Support Programmesmentioning
confidence: 99%
“…With the exception of the general characteristics of implementations, which are widely described in review studies (e.g., Gilligan et al, 2019;Li et al, 2021;Park, 2021), few results are reported on aspects relating to the institutional and external support that is required to boost the effectiveness of implementations. This leads to a current dilemma on the scientific dissemination of evidence-based programmes.…”
Section: Scaling Up In Communities and Services In Family Support Pro...mentioning
confidence: 99%
“…Although the quality standards related to programme evaluation are well known, there is not much empirical evidence about the extent to which family support programmes meet these criteria. To some extent, this lack of information is due to the fact that having a rigorous evaluation design (RCT or quasi-experimental with control group) is usually an inclusion criterion in meta-analyses and systematic reviews on the effectiveness of family support programmes (e.g., Arnason et al, 2020;Jeong et al, 2021;Li et al, 2021;Magioni & Williams, 2016;Rayce et al, 2017;Sama-Miller et al, 2019), thus programme evaluation studies that do not meet these quality standards are not usually published in peer-reviewed journals. This fact also explains that, in the review conducted by Barlow and Coren (2018) only six systematic reviews of the effectiveness of parenting programmes published in the Campbell Library were identified.…”
Section: Quality Standards Related To Programme Evaluationmentioning
confidence: 99%
“…At the broader intervention development level, recent efforts have focused on comprehensive modifications, guided by stakeholder consultation to improve outcomes [ 93 ]. For example, Triple P follows a process of partnering with community stakeholders to identify adaptations that meet the community's needs [ 16 , 94 ]. Adaptations include delivery in community centres, providing culturally relevant rationales for strategies, and the omission of topics deemed less culturally relevant (e.g.…”
Section: Addressing Parent Factors and Reducing Barriers To Treatment...mentioning
confidence: 99%